Persepsi Pejalan Kaki Terhadap Trotoar Di Lapangan Merdeka Kota Medan - Simanjuntak, Johan Oberlyn; Saragi, Tiurma Elita; Simanjuntak, Nurvita Insani M.; Laoli, Titusman Berkat (Jurnal Visi Eksakta, 2021)
Merdeka Square is one of the icons of Medan City which is continously visited by communities of Medan City or immigrant communities because Medan City is the capital of North Sumatera Province with a high complexity of activities in it. Improvements to the road transportation system facilities, especially sidewalk facilites, are important because the purpose of implementing sidewalks is as a special pedestrian lane with security and safety guarantees against traffic accidents. This study aims to look at people’s perceptions as the main users of sidewalk facilities so that they can encourage people to carry out walking activities as a basic moda of transportation. This research was conducted with a quantitative approach with accidental sampling method, namely primary data is the result of direct interviews in the field to the public using sidewalk facilities at Merdeka Square, Medan City. Based on the result of the analysis conducted on the results of the interview, it was found that the community as users of the sidewalks were not satisfied with the existing sidewalks facilities. So this study aims to provide input in order to improve sidewalk facilities that provide comfort and safety values for pedestrians in order to encourage and increase the number of pedestrians, especially at Merdeka Square, Medan City.